Combined convective and radiative heat transfer on transpiration cooling system in Al-Co open-celled foam having PPI of 20 - Amatachaya, Pipatana; Krittacom, Bundit; Peamsuwan, Rapeepong (Asia-Pacific Journal of Science and Technology, 2017)
One-dimensional transpiration cooling system in open-celled foam has been conducted experimentally and numerically to investigate the heat transfer characteristics of combined convection and radiation. The Alumina–Cordierite (Al-Co) open-cell foam having porosity of 0.875 and pores per inch (PPI) of 20 was employed. The upper surface of porous plate was heated by the heat flux of incoming radiation (qRx,f) varying from 0.97 - 16.59 kW/m2 whereas air injection velocity (uf) fed into the lower surface was varied from 0.364 - 1.274 m/s, and was then rearranged as Reynolds number (Re). For the report of the results in the present study, two efficiencies including of temperature (hT) and conversion efficiency (hC) were presented. The hT increased rapidly with the air injection velocity (Re). It was then saturated and had a constant value at Re higher than 15. For the result of hC, it was decreased slightly with increasing of qRx,f and uf (Re). The numerical predictions also agreed with experimental data very well.